2014
DOI: 10.1016/j.chom.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Human Microbiome Project: Dynamic Analysis of Microbiome-Host Omics Profiles during Periods of Human Health and Disease

Abstract: Much has been learned about the diversity and distribution of human-associated microbial communities, but we still know little about the biology of the microbiome, how it interacts with the host, and how the host responds to its resident microbiota. The Integrative Human Microbiome Project (iHMP, http://hmp2.org), the second phase of the NIH Human Microbiome Project, will study these interactions by analyzing microbiome and host activities in longitudinal studies of disease-specific cohorts and by creating int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
225
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(229 citation statements)
references
References 78 publications
3
225
0
1
Order By: Relevance
“…Over the past decade, many advances have been made in understanding the composition and structure of the microbiome (Integrative, 2014). Only recently however, has attention switched to understanding the function of the individual components of the microbiota, that is, the microorganisms themselves and the molecules they produce.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, many advances have been made in understanding the composition and structure of the microbiome (Integrative, 2014). Only recently however, has attention switched to understanding the function of the individual components of the microbiota, that is, the microorganisms themselves and the molecules they produce.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis highlights the extent of similarities in longitudinal omics profiles across individuals, as well as individual-specific signatures at steady state and under experimental perturbations. To further qunatify these differences, projects have been initiated to extend such analyses to thousands of individuals, characterizing preterm births, inflammatory bowel disease and type 2 diabetes 53 . In a similar vein, two separate groups recently profiled genetic and metabolomics data: one of these calculated polygenic risk scores for over 100 individuals and correlated these with measurements of metabolites 54 , whereas the other identified rare deleterious variants in healthy volunteers that correlated with outliers of individual metabolites and metabolic pathways 55 .…”
Section: Narrowing Causal Mechanisms In Common Diseasementioning
confidence: 99%
“…Above we have shown that to understand the role that organisms play in health and disease, we should move towards functional analysis of the communities, rather than focus on microbial composition. In fact, the second phase of the NIH Human Microbiome Project (Integrative Human Microbiome Project, iHMP, http://hmp2.org) will study the interactions between the microbiome and host in longitudinal studies by analyzing host-microbiome activities [70]. To this day, most of the ‘-omics’ studies have been focused on organisms, genes, or pathways rather than on the system as a whole.…”
Section: Future Directions and Challengesmentioning
confidence: 99%